The relationship between childhood trauma experiences and suicidal risk behavior - Corral Proaño, Verónica Jazmín (2017)
This investigation evaluated the relation between adverse childhood experiences and suicidal risk behavior in teenagers whose ages are between 13 and 18 years old and who are patients at “Servicio de Rehabilitación y Salud Mental del Hospital General Enrique Garcés” in 2016. The general objective was to analyze the relation between both variables through the lens of attachment theory and the hypothesis proposes that adverse childhood experiences trigger a higher probability of suicidal risk. The methodology combines a quantitative and a qualitative part; it was used the ACE questionnaire developed by Centers for Disease Control and Prevention (2016), which analyzes the adverse childhood experiences level, and the Attachment Script Assessment (ASA), developed by Rodrigues-Doolabh, Wais, Zevallos y Rodrigues (2001) to determine the attachment type. The results show that adverse childhood experiences cause injurious behaviors; the lack of a secure base in childhood makes the trauma experience the most intense; the risk factor the most evident is the familiar one (insecure attachment) related to violent behavior, psychological, physical mistreatment, neglect.